The Histone H3 Lysine 4 Presenter WDR5 as an Oncogenic Protein and Novel Epigenetic Target in Cancer - Lu, Kebin; Tao, He; Si, Xiaomin; Chen, Qingjuan (Frontiers in Oncology, 2018)
By forming protein complexes with histone H3 lysine 4 (H3K4) methyltransferases including MLL1-MLL4, the H3K4 presenter WDR5 plays a key role in histone H3K4 trimethylation, transcriptional activation of target genes, normal biology and diseases such as MLL-rearranged leukemia. By forming protein complexes with other proteins such as Myc, WDR5 induces transcriptional activation of key oncogenes, tumor cell cycle progression, DNA replication, cell proliferation, survival, tumorigenesis, progression, invasion and metastasis of cancer of a variety of organ origins. Several small molecule MLL/WDR5 protein-protein interaction inhibitors, such as MM-401, MM-589, WDR5-0103, Piribedil and OICR-9429, have been confirmed to reduce H3K4 trimethylation, oncogenic gene expression, cell cycle progression, cancer cell proliferation, survival and resistance to chemotherapy without general toxicity to normal cells. Derivatives of the MLL/WDR5 interaction inhibitors with improved pharmacokinetic properties and in vivo bioavailability are expected to have the potential to be trialed in cancer patients.